Boosting the Performance of Organic Optoelectronic Devices Using Multiple‐Patterned Plasmonic Nanostructures. Issue 25 (4th May 2016) - Lee, Yoon Ho; Lee, Tae Kyung; Song, Inho; Yu, Hojeong; Lee, Jiwon; Ko, Hyunhyub; Kwak, Sang Kyu; Oh, Joon Hak
Abstract : Multiple‐patterned nanostructures prepared by synergistically combining block‐copolymer lithography with nano‐imprinting lithography have been used as back reflectors for enhancing light absorption in organic optoelectronic devices. The multiple‐patterned electrodes have significantly boosted the performance of organic photovoltaics and phototransistors, owed to the highly effective light scattering and plasmonic effects, extending the range of their practical applications.